'The SEND Code of Practice has given me clout': a phenomenological study illustrating how SENCos managed the introduction of the SEND reforms. (28th January 2019) - Curran, Helen
Abstract : The introduction of the Special Educational Needs and Disabilities (SEND) reforms were hailed in 2014, by the then Government, as the most significant change to SEND policy for 30 years. Despite the changes introduced, the 2015 Code continued to place responsibility for the co‐ordination of provision for children with special educational needs within the remit of the SENCo. This article forms part of a wider study which examined the role of the SENCo at this time of significant reform; the study aimed to understand the role of the SENCo as a policy actor tasked with policy implementation, as well as their perceptions of the impact during the first year of reform. This article discusses the themes that arose from the in‐depth semi‐structured interviews carried out with SENCo participants during 2014/2015, which explored reflections on the SENCo role, SENCo activities undertaken across the year, and how SENCos facilitated the implementation of the 2015 Code.